The demand and supply of money under high inflation: Brazil 1974/94 - Octávio Augusto Fontes Tourinho (Institute for Applied Economic Research (ipea), 2015)
A specification for the demand for money in economies where inflation is high and stochastic is presented. It uses a generalized functional form and includes the variance of the inflation rate as an explanatory variable, and is estimated for Brazil in the period 1974/94 under the assumption that the monetary policy is passive and that expectations are adaptive. The supply of money is then specified as a generalization to a stochastic environment of the rule proposed by Sargent and Wallace (1973). The money demand and supply equations are then estimated simultaneously, under rational expectations, by using the Johansen (1991) (VEC) procedure and interpreting the two cointegrating vectors which arise as the supply and demand equations. The restrictions suggested by the hypothesized theoretical models for the money market equilibrium in high inflation processes are tested and accepted for this data.
Keywords: 330